STUDENTS’ PERCEPTIONS TOWARD READING NARRATIVE TEXT BY USING SKIMMING STRATEGY - Oping Sofiah (Journal of English Education Program (JEEP), 2020)
This paper was reports on the students’ perceptions toward reading narrative text by using skimming strategy and the problem solving of skimming strategy in reading narrative text. The method used in this research was qualitative research design focusing on the survey study. The population of this study were the students of tenth grade of an Islamic High School in Ciamis, and the researcher selected all class, which was MIPA 1, MIPA 2, IIK 1, and IPS 1, for a total of 89 students as the sample. The researcher used questionnaire and interview for technique of collecting data. The result of this research revealed that students react positively. From the questionnaire the researcher conluded that the students gave positive perceptions about reading narrative text by using skimming strategy. More significantly, students argue on the problem solving of skimming strategy in reading narrative text that was undertaken by interview. The problem solving of skimming strategy in reading narrative text for students was identifying purposes and organizational patters of texts, was understanding unknown vocabulary from structural clues and word parts, inferring information from the passage, understanding facts and details from the text, defining author’s attitudes, tones, and purposes on the passage. This can be noted that skimming strategy in reading narrative text was effective and efficient to be implementing in teaching English. Keywords: Reading Strategy, Skimming Strategy, Narrative Text, Perceptions.